Analyzing the Influence of Change Readiness on Change-Supportive Behavior in Health Information Systems - Wardani, Ratna; Wulandari, Laili; Safitri, Endah Wulan; Pratiwi, Rifka Sari (Journal of Digital Business and Innovation Management, 2025)
The main objective of this study was to assess the effect of communication quality and trust on behavior change, which supports the information system of health workers in public health centers through the mediating variable of readiness for change. Data were collected from 341 health workers working in public health centers in Indonesia through enumerators as data collectors. The statistical procedure is divided into descriptive analysis using SPSS 25 and structural equation model using bootstraps using Smart PLS 3.2.9. Structural Equation Model analysis found several results. The results positively affect the quality of communication, trust, willingness to change, and support for behavior change. In addition, the study readiness to mediate changes in communication quality and trust in supporting behavior change. Therefore, this study shows that the quality of communication and trust is significantly associated with behavioral changes that support the mediation readiness for change in health workers in East Java, Indonesia.The main question of this study is to assess the effect of communication quality and trust on behavioral change that supports the information system of health workers at public health centers through the variable of mediation readiness for change. Research has been conducted to answer this research question. It has been empirically proven that the quality of communication and trust affects changes in supportive behavior with and without mediation. We believe that the quality of communication and trust due to the combined effect of readiness for change produces behavioral changes that favor more than the quality of communication and trust itself.